X-ray inhibits FUT4-mediated proliferation in A549 cells by downregulating SP1 expression - Jin-xiao Liang; Gao, Wei; Wei, Wei-tian; Yang, Xun; Liu, Jin-shi (Journal of the Pakistan Medical Association, 2023)
Objective: To identify the mechanism of down-regulation of Lewis Y antigen caused by X-ray irradiation. Method: The present original research study was conducted at Zhejiang University City College, Hangzhou, Republic of China, from 2020 to 2022. Western blotting, Co-immunoprecipitation (CO-IP), electrophoretic mobility shift assay and Cell Counting Kit-8 (CCK8) were performed to confirm the effect of X-ray irradiation on A549 cell proliferation and its mechanism. Data was analysed using Statistical Package for Social Sciences (SPSS) 11.5. Results: The expressions of fucosyltransferase IV and Lewis Y were decreased after X-ray irradiation, thus inhibiting the proliferation of A549 lung cancer cells. Deoxyribonucleic acid damage caused by the irradiation caused higher level of poly- adenosinediphosphate-ribosylated Specific Protein 1(SP1), and translocation of SP1 from the nucleus, decreasing the expression of fucosyltransferase IV and Lewis Y. Conclusion: There was a significant role of glycosylation in radiation therapy for lung cancer. Key Words: Fucosyltransferase 4, SP1, X-ray, Lung cancer, Cell proliferation.